Towards a New Interpretation of Horkheimer´s Stance towards Science and Technology in the Context of his Critique to Positivism - García Cherep, Paula (2022)
Towards a New Interpretation of Horkheimer´s Notions of Science and Technique in the Context of his Critique to Positivism Paula García Cherep1Adriana Gonzalo2 Abstract: This paper discusses scholarly interpretations according to which in 1937 a radical shift in Horkheimer´s thought can be observed. This shift consists of a growing mistrust in science and technology, and a pessimistic view concern¬ing the possibilities of social transformation. Our purpose is to refute this inter¬pretation and to defend the hypothesis of absence of a negative perspective of the role of science and technology in that period. We aim to contrast the criticism of the position of positivism in relation to science and technology and the one de¬fended by Horkheimer. For this purpose, we will examine a set of Horkheimer?s texts from the forties. We focus on the topics related to his stance on science and its demarcation from metaphysics, the role of science and technology in capital-ist society, and the possibility of scientific progress and social transformation. In relation to the last topic, we argue that even if Horkheimer has always been faithful to a social transformative goal, he does not defend this goal from a blindly optimistic perspective. We will also consider the role of technology in Horkheimer?s thought regarding the social task of critical theory. In this sense, we will point out that Horkheimer?s view of science should be interpreted as nei¬ther negativist nor hopeless but must be considered in light of a new position regarding the relationship between the human being and nature. The last part of the article intends to be a contribution upholding the thesis that the notion of reason emerging from Horkheimer?s analysis is linked to a new idea of science based on a relation of non-domination of nature.